2015
DOI: 10.1093/nar/gkv653
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b/Tet1 regulatory axis epigenetically modulates mesendoderm differentiation in mouse embryonic stem cells

Abstract: Ten eleven translocation (Tet) family-mediated DNA oxidation on 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) represents a novel epigenetic modification that regulates dynamic gene expression during embryonic stem cells (ESCs) differentiation. Through the role of Tet on 5hmC regulation in stem cell development is relatively defined, how the Tet family is regulated and impacts on ESCs lineage development remains elusive. In this study, we show non-coding RNA regulation on Tet family may contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…A combined approach involving assessment of miR expression (using microarrays) and bioinformatic prediction of miR targets has revealed that distinct miR signatures fine-tune each step of malignancies; in turn, miRs that target critical suppressors could act as powerful proto-oncogenes. Several miRs, including miR-22, miR-29b and miR-26a, exert control by negatively regulating TET protein levels in mouse and human 45 - 47 . In this study, we demonstrated that both miR-26b-5p and miR-29c-5p silenced TET2 expression, whereas LSH was not recruited to the promoters of TET2 and TET3, providing a novel finding that LSH upregulated TET2 expression by silencing the expression levels of miRs.…”
Section: Discussionmentioning
confidence: 99%
“…A combined approach involving assessment of miR expression (using microarrays) and bioinformatic prediction of miR targets has revealed that distinct miR signatures fine-tune each step of malignancies; in turn, miRs that target critical suppressors could act as powerful proto-oncogenes. Several miRs, including miR-22, miR-29b and miR-26a, exert control by negatively regulating TET protein levels in mouse and human 45 - 47 . In this study, we demonstrated that both miR-26b-5p and miR-29c-5p silenced TET2 expression, whereas LSH was not recruited to the promoters of TET2 and TET3, providing a novel finding that LSH upregulated TET2 expression by silencing the expression levels of miRs.…”
Section: Discussionmentioning
confidence: 99%
“…; Tu et al . ). The reciprocal changes of miR‐210 and TET1 in uterine arteries of hypoxic animals suggest that miR‐210 may negatively regulate TET1 expression.…”
Section: Discussionmentioning
confidence: 97%
“…There have been many studies on miR-29b/TET1 being clearly associated with cell development [ 47 ]. In one study, Tu et al found that miR-29b regulation of TET1 contributed to epigenetic regulation during ESC differentiation [ 48 ]. In another study, Morita et al reported that miR-29b directly inhibited TET1 to repress the activity of DNA demethylases [ 49 ].…”
Section: Discussionmentioning
confidence: 99%